'Partnerships are crucial': an evaluation of the Aboriginal Family Birthing Program in South Australia. (20th November 2016) - Middleton, Philippa; Bubner, Tanya; Glover, Karen; Rumbold, Alice; Weetra, Donna; Scheil, Wendy; Brown, Stephanie
Abstract: Objectives: To evaluate implementation and outcomes of the Aboriginal Family Birthing Program (AFBP), which provides culturally competent antenatal, intrapartum and early postnatal care for Aboriginal families across South Australia (SA). Methods: Analysis of births to Aboriginal women in SA 2010–2012; interviews with health professionals and AFBP clients. Results: Around a third of all Aboriginal women giving birth in SA 2010–2012 (n=486) attended AFBP services. AFBP women were more likely to be more socially disadvantaged, have poorer pregnancy health and to have inadequate numbers of antenatal visits than Aboriginal women attending other services. Even with greater social disadvantage and higher clinical complexity, pregnancy outcomes were similar for AFBP and other Aboriginal women. Interviews with 107 health professionals (including 20 Aboriginal Maternal and Infant Care (AMIC) workers) indicated differing levels of commitment to the model, with some lack of clarity about AMIC workers and midwives roles. Interviews with 20 AFBP clients showed they highly valued care from another Aboriginal woman. Conclusions: Despite challenges, the AFBP reaches out to women with the greatest need, providing culturally appropriate, effective care through partnerships. Implications for Public Health: Programs like the AFBP need to be expanded and supported to improve maternal and child health outcomes for Aboriginal families.